STUDI TENTANG PROFESIONALISME APARATUR DALAM PELAKSANAAN GOOD GOVERNANCE DI KEC. LINGGANG BIGUNG, KAB. KUTAI BARAT - Marlin Marlianti (Jurnal Paradigma (JP), 2017)
To realize the good governance in subdistrict Linggang Bigung, government should enhance the degree of professionalism of apparatus in local level. The determinant factors of professionalism are knowledge, ability and equality. This article is a description about the study of apparatus professionalism in subdistrict Linggang Bigung. Implementing good governance is very necessary in modern bureaucracy, it does not only give priority the capability to conduct duties and organizational function, but it has also the capability to response public aspiration, that is what we call by professionalism.